Understanding the Potential and Risk of Bacterial Siderophores in Cancer - Pita-Grisanti, Valentina; Chasser, Kaylin; Sobol, Trevor; Cruz-Monserrate, Zobeida (Frontiers in Oncology, 2022)
Siderophores are iron chelating molecules produced by nearly all organisms, most notably by bacteria, to efficiently sequester the limited iron that is available in the environment. Siderophores are an essential component of mammalian iron homeostasis and the ongoing interspecies competition for iron. Bacteria produce a broad repertoire of siderophores with a canonical role in iron chelation and the capacity to perform versatile functions such as interacting with other microbes and the host immune system. Siderophores are a vast area of untapped potential in the field of cancer research because cancer cells demand increased iron concentrations to sustain rapid proliferation. Studies investigating siderophores as therapeutics in cancer generally focused on the role of a few siderophores as iron chelators; however, these studies are limited and some show conflicting results. Moreover, siderophores are biologically conserved, structurally diverse molecules that perform additional functions related to iron chelation. Siderophores also have a role in inflammation due to their iron acquisition and chelation properties. These diverse functions may contribute to both risks and benefits as therapeutic agents in cancer. The potential of siderophore-mediated iron and bacterial modulation to be used in the treatment of cancer warrants further investigation. This review discusses the wide range of bacterial siderophore functions and their utilization in cancer treatment to further expand their functional relevance in cancer detection and treatment.